2022
DOI: 10.2991/assehr.k.211229.021
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Financial Literacy in Mathematics Education: Proposed Design for Instruction

Abstract: This study aims to develop a social arithmetic learning design by integrating Islamic economic principles. Using various Islamic financial products as a context in mathematical tasks, we propose a hypothetical learning trajectory (HLT) to support the students' Islamic financial literacy (IFL) skills. We chose design research as the method to achieve the goal. However, we limit the discussion to a part of one phase, namely pilot experiments, of the three main phases of design research. This study involves six s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This section will describe how mathematical tasks integrated with IFL were developed using the MIFL framework. See Kusumawati et al (2021) from the study on the development of the MIFL (content domain) framework for further information on our research into the framework's development. Following that, we will describe the initial tasks and HLT that was compiled based on the results of the literature review.…”
Section: Preparing For Experiments and Preliminary Designmentioning
confidence: 99%
See 2 more Smart Citations
“…This section will describe how mathematical tasks integrated with IFL were developed using the MIFL framework. See Kusumawati et al (2021) from the study on the development of the MIFL (content domain) framework for further information on our research into the framework's development. Following that, we will describe the initial tasks and HLT that was compiled based on the results of the literature review.…”
Section: Preparing For Experiments and Preliminary Designmentioning
confidence: 99%
“…The use of contextual problems helps students improve their mathematical abilities (Doorman & Gravemeijer, 1999). Additionally, the learning design with contextual problem integrated has the potential to enhance students' fundamental mathematical capabilities, such as reasoning, argumentation, and mathematizing (Kusumawati et al, 2022). Numerous studies have demonstrated that contexts can improve students' mathematical comprehension, including historical ones, (Fachrudin et al, 2019;2020a;2020b), culture-based context (Samo, Darhim, & Kartasasmita, 2018), Indonesian traditional game (Jaelani et al, 2013) and even in a financial context (Sawatzki, 2017).…”
Section: Teachermentioning
confidence: 99%
See 1 more Smart Citation
“…According to Darmawan (2021), financial mathematics involves the use of mathematical concepts to analyze, understand, and make decisions related to financial aspects such as investments, loans, risks, and long-term financial planning. Understanding financial mathematics provides a strong foundation for managing personal finances wisely (Kusumawati, 2021). Through an understanding of concepts such as interest, discount, and time value of money, individuals can make smarter decisions regarding savings, investments, and debt (Hamidah, 2020).…”
Section: Introductionmentioning
confidence: 99%